When Communicative Worlds Collide: Strategies for Negotiating Misalignments in Attentional Social Presence - Jeanine Warisse Turner; Sonja K. Foss (Philosophies)
A significant issue facing communicators in the current multicommunicative environment is securing the attention of potential audience members who are likely to be engrossed in their digital devices. The theory of attentional social presence suggests that communicators secure their attention using one of four types of social presence—budgeted, competitive, entitled, and invitational. In this essay, the theory of attentional social presence is extended by identifying strategies interactants use to resolve misalignments in expected or preferred types of social presence. The research design involved interviews with 32 individuals about their experiences with misalignment in attentional social presence. Transcripts of the interviews were coded following the qualitative approach of grounded theory. Three primary strategies emerged from the analysis—prescribing to eliminate misalignment, rationalizing to overlook misalignment, and co-creating to resolve misalignment. Understanding various methods for negotiating mismatches among chosen types of social presence will allow communicators to create more satisfying and productive interactions.